Uso de mapa de vulnerabilidade ambiental como ferramenta de planejamento urbano : ocupação da Bacia do Córrego Mauá, Sarandi - Paraná - Serrano, Danilo Giampietro (2011)
The concern with urban planning and the rational search for new areas for urban expansion, with positive indicators, has been more looking for nowadays. This happens because the sustainability policy demand a appropriate interaction between man and the environment; the environmental impacts and their agents can change to review and have attracted interests around the world in the search of solutions, enabling the coexistence of man with environment. This is due in the requirement of studies and research about the structure and dynamics of the environment and your potentiality and or vulnerability in relation of introduction of news activities, even in not planned cities. At this point, the study and the use of System of Geographic Information - SGI combined with geotechnical investigation can mean progresses in the right occupation of urban areas, in priority areas, especially when is in front of historic of occupation of the Sarandi city, Paraná. On this hand, based on the study aims that is to draw a map of environmental erodibility, was developed and systematized a map of environmental vulnerability on Mauá Basin Creek, on the city of Sarandi, which is considered an area of urban expansion. Using the Nakashima (1999) methodology to the systematization of the work and using the methodology proposed by Crepani et al. (2001) to development of vulnerability map, both of them with some modifications. On this way, realized that for the Mauá Basin Creek, Sarandi/PR, the map of environmental vulnerability is an important tool for a urban and rural planning, in order to guide the urban expansion on new areas, allowing, according to the environmental preservation, the ration and proper user for a management of areas unfavorable to certain types of use land and soil.